KARAKTERISTIK SIFAT KIMIA TANAH KELAPA SAWIT MENGHASILKAN DAN SISIPAN PADA TUTUPAN LAHAN SUB DAS SUNGAI BARUMUN DESA TANJUNG MEDAN - Armindo Dwi Alan MV; Fitra Syawal Harahap; Khairul Rizal; Ika Ayu Putri Septyani (Agros Journal of Agriculture Science, 2023)
A watershed (DAS) is an ecosystem unit consisting of natural resources such as soil. Watersheds are influenced by the physical, chemical and biological properties of the soil that support the soil to carry out its various functions. The purpose of this study was to determine the nutrient status of oil palm plants during the first generation, and to analyze the physical properties of the soil, texture, water content, effective depth of cover. Berumun River sub-watershed area. The location of this research was in the Barumun River, Tanjung Medan Village, Kampung Rakyat District, South Labuhanbatu Regency. The city is between 99₀44'E - 100₀26'E and 1₀26'N -20₀15'N . This study used a field survey method directly. At the research location and soil sampling was carried out statistically, the distance between the sampling points from one another was carried out based on the conditions of the survey area. This study showed that the chemical properties of the soil in Tanjung Medan Village pH-H2O 5.0-5.55 (mass), N 0.07-0.15 (very low), C-Oorganic 0.69-1.82 (low ), P 32.47-79.94 (very high), K 0.43-0.71 (moderate), Ca 0.35-0.73 (moderate), Mg 0.88-1.93 (moderate) , Na 0.41-0.72 (medium). The condition of oil palm stands in the Das River Basin in Tanjung Medan Village, Kampung Rakyat Subdistrict, South Labuhanbatu Regency still requires fertilization surveys at several points lacking in nutrients in order to optimize nutrient content in the soil for optimal results Keywords: characteristics, properties, chemistry, soil, oil palm.INTISARIDaerah aliran sungai (DAS) merupakan satu kesatuan ekosistem yang terdiri dari sumberdaya alam seperti tanah. DAS dipengaruhi oleh sifat fisika, kimia maaupun biologi tanah yang mendukung tanah untuk melakukan berbagai fungsinya.Tujuan penelitian ini untuk mengetahui status unsur hara pada tanaman kelapa sawit pada masa generasi pertama, Dan menganalisis sifat fisik tanah,tekstur, kadar air, kedalaman efektif pada tutupan lahan Sub DAS Sungai Berumun. Tempat penelitian ini dilakukan di Sungai Barumun Desa Tanjung Medan, Kec Kampung Rakyat, Kabupaten Labuhanbatu Selatan. Kota ini berada antara 99₀44’BT - 100₀26’BT dan 1₀26’LU -20₀15’LU . Penelitian ini menggunakan metode survei lapangan secara langsung. Pada lokasi penelitian dan pengambilan sampel tanah dilakukan secara statistik, jarak antara titik pengambilan sampel satu dengan yang lainnya dilakukan berdasarkan kondisi wilayah survei. Penelitian ini menunjukan bahwa sifat kimia tanah pada Desa Tanjung Medan pH-H2O 5,0-5,55 (massam), N 0,07-0,15 (sangat rendah), C-OOrganik 0,69-1,82 (rendah), P 32,47-79,94 (sangat tinggi), K 0,43-0,71 (Ssedang), Ca 0,35-0,73 (sedang), Mg 0,88-1,93 (sedang),Na 0,41-0,72 (sedang). Kondisi tegakan kelapa sawit di Daerah Aliran Sungai Das di Desa Tanjung Medan Kecamatan Kampung Rakyat Kabupaten Labuhanbatu Selatan masih memerlukan survei pemupukan pada beberapa titik yang kekurangan unsur hara supaya mengoptimalkan kandungan unsur hara pada tanah supaya hasil yang optimal Kata Kunci: karakteristik, sifat, kimia, tanah, sawit.